Pendampingan Branding UMKM Makanan Ringan Melalui Pengelolaan Media Sosial - Bocca Della Verita; Poppy Febriana; Ainur Rochmaniah (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The existence of technological developments can help all aspects of human life, includ-ing for business person. One place that can be utilized is social media. Social Media has a great opportunity to help MSMEs as a marketing tool for their products to a wider scope and create business competition in today's digital era. However, there are also many business person who still cannot balance their business with the arrival of the digi-talization era, as happened with "Tahu Fantasi Kuy" and "Chancaroon" MSMEs. Both of them carry out promotions in a conventional way and with unattractive product photos, so that point become an inhibiting factor for the progress of their business. By using lecture, simulation and question answer methods, this community service aims to provide businesses with an understanding of the importance of branding and online marketing in the digital era. After the mentoring activities for MSME snacks were carried out, the two business actors understood how to build business branding digitally by utilizing Instagram and presenting attractive product photos so as to create increased sales figures